Evocacion Sentimental de Colombia y de Algunos Escritores Colombianos - Garces, Cristobal (Revista Universidad de Guayaquil, 1998)
I begin by making a categorical confirmation: in this V Meeting of the Word, the hands of Otto Morales Benítez and the Devil must undoubtedly be at work. Because; how can one explain that, in a town in the Colombian province, quite far from easy and comfortable routes, an intelligence festival is taking place? Moreover, it has managed to gather people who have come from the warm Atlantic coasts, like that miracle of light turned into song that is Meira Delmar, who rightfully deserves to carry the denomination of Meira of Colombia, the immortal. And also, from that ’high and somber Bogotá,’ as this vagabond who speaks to you today once sang, has arrived that voice, transparent, simple, and sensitive like a newly born spring, just like the poetry of Maruja Vieira. She has inspired my muse on more than one occasion, from the very first moment I breathed in the invigorating atmosphere of Bogotá, the beloved city of my affection.